The role of CD30 and CD153 (CD30L) in the anti-mycobacterial immune response. (January 2017) - Marín, Nancy D.; García, Luis F.
Abstract: The establishment of a protective T-cell response against mycobacterial infections involves different co-stimulatory molecules and their respective ligands. Among these molecules the Tumor Necrosis Factor Receptor Super-family (TNFRSF) and the Tumor Necrosis Factor Super-family (TNFSF) are known to be important members. This review analyzes the evidence that CD30 and CD153 (CD30L), members of the TNFRSF and TNSF, play key roles in the T cell-dependent anti-mycobacterial immune response. Mice deficient in either CD30 or CD153, or treated with antibodies blocking the effects or CD30 and CD153, and infected with M.avium or M.bovis BCG exhibit higher bacterial burden, abnormal inflammatory responses with decreased Th1 responses, this is evidenced by the reduced number of IFN-γ-producing cells. Recent evidence also showed that CD30 + CD153 + Tγδ cells participate in the early stages of M.bovis BCG infection by producing IL-17A. In humans, stimulation of T-cells with mycobacterial antigens induces CD30 expression mainly by CD4 + cells; CD30 + cells have been demonstrated in tissues of patients with tuberculosis (TB) and in positive tuberculin skin test reactions. In addition, the levels of soluble CD30 are increased in serum and BAL of TB patients and these levels seems to correlate with the severity of the disease. These findings suggest that CD30/CD153 interactions during the anti-mycobacterial immune response are important for the establishment and maintenance of a protective response. Further studies would be required to determine whether these molecules may be good clinical biomarkers or potential targets for immune manipulation.